Reduction of Relapse after Unrelated Donor Stem Cell Transplantation by KIR-Based Graft Selection - Heidenreich, Silke; Kröger, Nicolaus (Frontiers in Immunology, 2017)
Beside donor T cells, natural-killer (NK) cells are considered to have a major role in preventing relapse after allogeneic hematopoietic stem cell transplantation (HSCT). After T-cell depleted haplo-identical HSCT, a strong NK alloreactivity has been described. These effects have been attributed to killer-cell immunoglobulin-like receptors (KIR). Abundant reports suggest a major role of KIR on outcome after haploidentical HSCT, but also in the unrelated donor setting. Within this review, we give a brief overview of the mechanism of NK-cell activation, nomenclature of KIR haplotypes and human leucocyte antigen (HLA) groups and of distinct models for prediction of NK-cell alloreactivity. It can be concluded that KIR-ligand mismatch seems to provoke adverse effects in unrelated-donor HSCT with reduced overall-survival and increased risk for high-grade acute graft-versus-host disease. Presence of activating KIR, as seen in KIR haplotype B, as well as the patient´s HLA C1/x haplotype might reduce relapse in myeloid malignancies.